IMPLEMENTASI METODE ENTROPY DAN COPRAS UNTUK EVALUASI KINERJA PASOKAN SAYURAN PADA ROCKET CHICKEN AREA SEMARANG - Dinda Okta Via; Saifur Rohman Cholil (Universitas Stikubank, 2026)
The development of the fast-food culinary business in Indonesia, particularly the Rocket Chicken network in Semarang, requires optimal management of fresh vegetable raw material supply to maintain quality consistency and operational continuity. This study aims to evaluate vegetable supply performance at ten Rocket Chicken branches in the Semarang area by integrating the Entropy method for objective weighting and Complex Proportional Assessment (COPRAS) for alternative ranking. Data were collected through questionnaires from 34 respondents covering assessments of five main criteria (Price, Quality, Timeliness, Supply Continuity, Service and Responsiveness) as well as actual supplier performance assessments. The Entropy weighting results show Quality as the most important criterion (62.1%), followed by Supply Continuity (24.2%), Price (8.1%), Timeliness (4.0%), and Service (1.5%). The application of COPRAS, treating Price as a cost criterion and other criteria as benefits, yields the highest performance ranking at the MENOREH branch with a utility value of 1.0690 (100.00%), followed by TLOGOSARI (96.75%), MRICAN (96.00%), NGAILYAN (94.03%), and SEKARAN (92.64%). Validation using Spearman rank correlation shows methodological consistency with a coefficient of ρ = -0.939, indicating excellent results. The differences between Entropy and COPRAS results indicate different evaluation perspectives, where Entropy emphasizes information variation in data, while COPRAS focuses on cost-benefit combination optimization. This study provides practical contributions in the form of supply performance improvement priority recommendations focusing on vegetable quality enhancement and methodological contributions through the integration of Entropy-COPRAS proven effective for evaluating fresh food supply chain performance in the context of the Indonesian culinary business.